Ethylene insensitivity conferred by a mutated Arabidopsis ethylene receptor gene alters nodulation in transgenic Lotus japonicus - Lohar, Dasharath (Oxford University Press, 2009)
BACKGROUND AND AIMS: Transgenics are used to demonstrate a causal relationship between ethylene insensitivity of a seedling legume plant, the level of ethylene receptor gene expression, lateral root growth and Mesorhizobium loti-induced nodule initiation. METHODS: Lotus japonicus plants expressing the dominant etr1-1 allele of the Arabidopsis thaliana gene encoding a well-characterized mutated ethylene receptor were created by stable Agrobacterium tumefaciens transformation. Single insertion, homozygous lines were characterized for symbiotic properties. KEY RESULTS: Transgenic plants were ethylene insensitive as judged by the lack of the ‘Triple Response’, and their continued ability to grow and nodulate in the presence of inhibitory concentrations of ACC (1-aminocyclopropane-1-carboxylic acid; an ethylene precursor). Transgenic plants with high insensitivity to ACC had significantly fewer lateral roots and exhibited increased nodulation while showing no altered nitrate sensitivity or lack of systemic autoregulation. Whereas ACC-insensitive shoot growth and nodulation were observed in transformants, root growth was inhibited similarly to the wild type. Increased nodulation was caused by increased infection and a seven-fold increase in nodules developing between xylem poles. Bacteroid numbers per symbiosome increased about 1·7-fold in ethylene-insensitive plants. CONCLUSIONS: The study further demonstrates multiple roles for ethylene in nodule initiation by influencing root cell infections and radial positioning, independent of autoregulation and nitrate inhibition of nodulation.